2019
DOI: 10.1590/abd1806-4841.20197490
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of tacrolimus ointment for the prevention of hypertrophic scars in experimental model

Abstract: Background: Tacrolimus, for its activity on modulation of collagen production and fibroblast activity, may have a role in the prevention of hypertrophic scars. Objectives: Evaluate macroscopic, microscopic, metabolic, laboratory effects and side effects of the use of topical tacrolimus ointment, in different concentrations, in the prevention of hypertrophic scars. Methods: Twenty-two rabbits were submitted to the excision of 2 fragments of 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Both topical and intradermal tacrolimus treatment have been previously studied in HTSs using rabbit ear models, but their effects on pigmentation were not measured, and the model itself does not lend itself to the study of high FST skin 26–28 . Menezes et al and Gisquet et al both found a reduction in scar thickness and inflammatory cellular density in scars treated with tacrolimus compared to controls 26,28 . Immunohistochemical analysis of excised wounds after 30 days of 0.1% or 0.03% topical tacrolimus treatment showed decreased transforming growth factor‐b, a well‐known contributor to fibrosis in HTS, and smooth muscle actin expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both topical and intradermal tacrolimus treatment have been previously studied in HTSs using rabbit ear models, but their effects on pigmentation were not measured, and the model itself does not lend itself to the study of high FST skin 26–28 . Menezes et al and Gisquet et al both found a reduction in scar thickness and inflammatory cellular density in scars treated with tacrolimus compared to controls 26,28 . Immunohistochemical analysis of excised wounds after 30 days of 0.1% or 0.03% topical tacrolimus treatment showed decreased transforming growth factor‐b, a well‐known contributor to fibrosis in HTS, and smooth muscle actin expression.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Tacrolimus has been previously studied in a rabbit ear model of HTS, but evaluation of repigmentation was not included. [26][27][28] To our knowledge, the effect of tacrolimus on repigmentation in HTS has yet to be studied. If proven to be safe and efficacious, tacrolimus would provide a noninvasive method of promoting pigmentation hence relieving morbidity associated with dyschromic burn scars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Another study demonstrated the beneficial effects of topical tacrolimus ointment in preventing hypertrophic scars in rabbit models. 51 In an open-label pilot study, the majority of patients exhibited a decrement in induration, erythema, pruritus and tenderness after topical application of tacrolimus ointment (0.1%) twice a day for 12 weeks, yet no statistically significant benefits as a therapeutic agent were observed. 52 Another study showed the preventive role of topical tacrolimus against keloids in 25 patients after surgery.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 97%
“…A punch biopsy was the most common device used to make skin incisions, reported in 31 of the 35 studies. Four studies reported creating a circular incision but did not specify the type of device used (13)(14)(15)34). One study compared the scar result from using a biopsy device with a controlled thermal injury (18).…”
Section: Rabbit Modelsmentioning
confidence: 99%